IMPLEMENTASI PEMBERIAN GANTI RUGI DALAM PEMBEBASAN TANAH UNTUK PEMBANGUNAN JALAN TOL SOLO-KERTOSONO BERDASARKAN ASAS KESEJAHTERAAN MENURUT UNDANG-UNDANG NOMOR 2 TAHUN 2012 TENTANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - PURWANTA, PURWANTA (Dinamika Hukum, 2018)
The purpose of this study is to: 1) examines the implementation of reparation in the liberation of the land for the construction of toll roads, Solo- Kertosono, whether it is in compliance with the principle of welfare according to ACT No. 2 of the year 2012 On Land Procurement For Development For The Benefit Of The Public. 2) examines the factors that become advocates/barrier in the process of reparation in the construction of toll roads, Solo-Kertosono. The method of approach in writing this is the juridical sociological. The specification of this research uses descriptive analytic. Data source use the primary data and the data of skunder. Engineering data collection using the study interview, the library and study the documents. To analyze the data, the researchers used a qualitative descriptive methods of analysis. Based on the research results obtained conclusions that: 1) the implementation of reparation in the liberation of the land for the construction of toll for development for the benefit of common with reparation to the community that his rights to land affected by the construction of toll roads in the form of money damages. The magnitude of the money damages in the fulfillment of basic welfare performed with the value reparation the current market price, so that people who receive compensatory will experience economic improvement and kesejahteraannya, because the money the indemnity could be used to buy land and the rest for business activities. 2) factors that become advocates in the process of reparation in the construction of toll roads, Solo-Kertosono i.e. determination of the unsettled deliberations the magnitude of damages as well as the magnitude of damages set by the Government that is three times orders of magnitude greater than the market price of the land. Restricting factors in the process of reparation in the construction of toll roads, Solo-Kertosono namely rejection of the citizens of the community. Keywords: compensation, land acquisition, the basis of well-being